Thiocarboxylate-modified Ni(OH)2 nanosheets for high-performance alkaline batteries. Issue 35 (2nd September 2019) - Zhao, Hongyang; Yin, Dandan; Wang, Jianwei; Zheng, Yuansuo; Du, Yaping
Abstract : Thiocarboxylate-modified Ni(OH)2 nanosheets present a superior electrochemical performance as an alkaline rechargeable battery cathode due to their highly conductive metal–sulfur bonds. Abstract : Thiocarboxylate-modified Ni(OH)2 nanosheets were successfully constructed and show much enhanced electrochemical performance compared with Ni(OH)2 nanosheets. Structural and electrochemical characterization demonstrated that the unique coordination between the nickel and sulfur enhances the conductivity, and markedly improves the electrochemical kinetics. The design of using a sulfur-containing molecule shows promising potential in electrochemical energy storage applications.